Clostridium difficile Infection in Travelers—A Neglected Pathogen?. Issue 1 (4th December 2012) - Neuberger, Ami; Saadi, Tarek; Shetern, Anat; Schwartz, Eli
<x xml:space="preserve">Abstract</x> Background Until recently, Clostridium difficile infection (CDI) has been mostly diagnosed in hospitalized elderly patients treated with antibacterial agents. The epidemiology of C difficile is changing as the ribotype 027 strain is spreading worldwide, and more infections are diagnosed in patients residing in the community. Although only few data about the epidemiology of CDI in developing countries are available, a number of reports seem to indicate that the incidence of CDI may be high in some such countries. Transmission of CDI may be more common in hospitals that lack the resources for efficient infection control programs. Theoretically, travelers to low‐income countries may be exposed to C difficile both in the community and within hospitals. Methods Data for this article were identified by searches of PubMed and MEDLINE, and references from relevant articles using the search terms "clostridium" and "travel." Abstracts were included when related to previously published work. Results and conclusions A total of 48 cases of travelers with CDI were located. CDI among travelers was more commonly acquired in low‐ and medium‐income countries, although 20% of all reported cases occurred in travelers returning from high‐income countries. All travelers with CDI for whom a detailed history was available acquired the infection in the community. CDI in travelers occurred in relatively young patients and was frequently associated with the empiric use of antibacterial agents, notably fluoroquinolones. A sizable minority of travelers with CDI had no exposure to antibacterial agents at all. The incidence of travel‐related CDI is unknown, but may be higher than previously suspected. A prospective study among travelers with unexplained acute or chronic diarrhea is warranted.